Off-label drug in the newborn - Laura Cuzzolin (Journal of Pediatric and Neonatal Individualized Medicine, 2014)
The lack of specific drugs and labelling recommendations for the neonatal population is a long-standing problem throughout the world. With the introduction of the Paediatric Regulation in 2007, in Europe tangible steps have been made to increase clinical research in children, but only a limited number of clinical trials included neonates that remain therapeutic orphans. This leads to a widespread use of medicines outside the terms indicated in the product license (off-label as regards dose, route of administration, indication, age group) or in an unlicensed manner (formulations modified, extemporaneous preparations, imported medicines, chemicals used as drugs). This use, often made on the basis of a consolidated clinical experience in absence of other authorized options, does not imply that a drug is contraindicated or disapproved, but simply means that insufficient data are available to grant approval status and the risks and benefits of using a drug in a particular situation have not been examined. Given the importance that neonatal population not be denied of drugs that are clearly beneficial, an updated overview of the worldwide situation of off-label and unlicensed drug use in the newborn will be presented, by analyzing also the impact of recent legislative initiatives and the well recognized problems (increased risk of ineffective or toxic treatments, adverse drug reactions and medication errors).